Environmentally friendly high temperature resistant coated sand and preparation process thereof
By using epoxy resin and acid curing agent in the coating sand preparation process, combined with urea propyltriethoxysilane, composite fiber nanocrystalline aerogel and composite nanofluid, the problem of ulotropine decomposition and producing harmful gases is solved, and a high-temperature resistant and environmentally friendly coating sand is prepared.
Patent Information
- Application Number
- CN202211318575.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-26
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-10-26
AI Technical Summary
Ulotropine used in the existing coating sand preparation process will decompose and produce harmful gases, pollute the environment and endanger the health of workers.
The ortho-cresol epoxy resin is used as the binder, and the ring-opening reaction of epoxy groups is used to cure to avoid the release of harmful gases. The acid curing agent containing active hydrogen is used to replace ulotropine, and materials such as urea propyltriethoxysilane, composite fiber nanocrystalline aerogel and composite nanofluid are prepared to prepare environmentally friendly and high-temperature coating sand.
The preparation of environmentally friendly coated sand without ammonia gas emission has been achieved, with good high temperature resistance, strength and tensile strength, and meets environmental protection requirements.
Smart Images

Figure BDA0003910457530000081 
Figure BDA0003910457530000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of coated sand, and in particular to environmentally friendly, high temperature resistant coated sand and a preparation process thereof. Background Art
[0002] At present, the most widely used casting method is sand casting. With the rapid development of my country's automobile industry, casting technology has been continuously improved, and the application of coated sand shell casting technology has become more and more extensive. Compared with other sand materials such as clay sand and resin self-hardening sand, coated sand has the characteristics of low cost, good fluidity, easy filling and molding, low moisture absorption, and high precision. The castings produced are mainly used to produce more complex precision castings such as cast iron parts, pump parts, and automotive parts.
[0003] In the existing market, phenolic resin is mostly used to prepare coated sand, and the curing agent is mainly urotropine, i.e. hexamethylenetetramine. During the preparation process of coated sand, after heating, the phenolic resin melts and reacts with urotropine to cross-link to form a three-dimensional network structure. However, urotropine will also decompose to produce irritating and harmful gases such as ammonia, which pollutes the environment and also seriously endangers the health of practitioners. Summary of the invention
[0004] The purpose of the present invention is to provide an environmentally friendly, high temperature resistant coated sand and a preparation process thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A preparation process of environmentally friendly high temperature resistant coated sand, comprising the following steps:
[0007] The raw sand is dried, ureapropyl triethoxysilane is added and mixed, the temperature is raised to 140-150°C and transferred to a sand mixer, o-cresol epoxy resin and composite fiber nanocrystalline aerogel are added to mix the sand; the temperature is lowered to 125-130°C, composite nanofluid and curing accelerator are added and mixed, the temperature is lowered to 80-95°C, curing agent is added, sand is removed, crushed, sieved, vinyl silicone oil is added and mixed evenly, and an environmentally friendly and high temperature resistant coated sand is obtained.
[0008] The existing process adopts a non-phenolic resin system to prepare coated sand, and generally prepares phosphate inorganic coated sand by cold method and hot method, which reduces the gas emission of the coated sand, but the production process is more complicated, and there are disadvantages such as the core shooting and molding process are not easy to control; in the present invention, o-cresol epoxy resin is used instead of thermoplastic phenolic resin as a binder, and the resin is cured and formed by the ring-opening reaction of the epoxy group. The reaction process does not release small molecular harmful gases such as ammonia, which meets environmental protection requirements; and an acid curing agent containing active hydrogen is used instead of hexamethylenetetramine, and other additives are added to prepare environmentally friendly coated sand.
[0009] The molecular chain of o-cresol epoxy resin contains a phenolic structure and a large proportion of rigid benzene ring structure, so it has a high glass transition temperature, excellent heat resistance, mechanical strength and processing stability, and the melt viscosity of o-cresol epoxy resin is low, which is conducive to the coating process.
[0010] Furthermore, the raw material composition of the environmentally friendly and high temperature resistant coated sand is, by weight: 70-85 parts of raw sand, 0.5-1 parts of ureapropyl triethoxysilane, 15-25 parts of o-cresol epoxy resin, 1-3 parts of composite fiber nanocrystalline aerogel, 6-12 parts of composite nanofluid, 0.4-1 parts of curing accelerator, 5-10 parts of curing agent, and 0.5-1 parts of vinyl silicone oil.
[0011] Ureapropyltriethoxysilane is used as a silane coupling agent. Its molecules contain amino and imino structures, which can form hydrogen bonds with the oxygen in the o-cresol epoxy resin molecules, enhance the interaction force, and better combine with the resin, thereby improving the thermal strength of the coated sand.
[0012] Furthermore, the curing accelerator is 2-ethyl-4-methylimidazole, and the mass ratio of the curing accelerator to the curing agent is 8-10%.
[0013] 2-Ethyl-4-methylimidazole is used as a curing accelerator to reduce the curing time and temperature.
[0014] Furthermore, the curing agent is a compound of boric acid, citric acid and silicic acid in a mass ratio of 1:1:1.
[0015] However, the curing agent uses citric acid, which has the problem of moisture absorption, and vinyl silicone oil is added to improve the rust resistance of the coated sand.
[0016] Furthermore, the preparation of the composite fiber nanocrystalline aerogel includes the following steps: mixing and stirring the carboxymethyl chitosan and carboxylated fiber nanocrystalline suspension for 20-30 minutes, adding to an aqueous solution containing copper acetate monohydrate, standing, separating, and washing to obtain copper-based hydrogel balls; mixing the copper-based hydrogel balls, trimesic acid, deionized water, and ethanol, adjusting the pH value of the solution to 3.1, stirring for 1-2 hours, replacing the solvent with tert-butanol, and freeze-drying to obtain the composite fiber nanocrystalline aerogel.
[0017] Furthermore, the mass volume ratio of the copper-based hydrogel ball, trimesic acid, deionized water, and ethanol is 1 g:30 mg:10 mL:10 mL.
[0018] The composite fiber nanocrystal aerogel is introduced into the o-cresol epoxy resin to improve the high temperature resistance of the coated sand, and the introduction of the composite fiber nanocrystal aerogel can also be used as a binder for the original sand to improve the thermal strength of the coated sand; the composite fiber nanocrystal aerogel of the invention is a spherical material with a core-shell structure prepared by assembling the ionic crosslinking of divalent copper ions and carboxyl groups and the coordination bonding of divalent copper ions and trimesic acid organic ligands, the inner core is a three-dimensional network structure formed by fiber nanocrystals and carboxymethyl chitosan, which effectively improves the tensile strength and toughness of the coated sand; the outer shell structure is a dense MOF-199, which greatly improves the bonding degree between the composite fiber nanocrystal aerogel and the o-cresol epoxy resin and the original sand, thereby effectively improving the homogeneity of the coated sand.
[0019] Furthermore, the preparation of the composite nanofluid comprises the following steps:
[0020] 1) Tetrabutylphosphonium bromide, sodium 3-(benzothiazole-2-mercapto)propane sulfonate and methanol are mixed, stirred at 55-60° C. for 44-46 hours, filtered, acetonitrile is added, filtered, dichloromethane is added, washed with deionized water, and dried to obtain an ionic liquid;
[0021] 2) Grinding the ionic liquid and carbon nitride for 5-10 minutes, adding deionized water and continuing grinding for 5 minutes, and ultrasonically stirring for 20-30 minutes to obtain carbon nitride nanofluid;
[0022] 3) the ionic liquid and molybdenum disulfide were mixed and ground for 5-10 minutes, gum arabic and deionized water were added and ground for 5 minutes, and ultrasonically stirred for 20-30 minutes to obtain a molybdenum disulfide nanofluid;
[0023] 4) The carbon nitride nanofluid and the molybdenum disulfide nanofluid are mixed and ultrasonically stirred for 20-30 minutes to prepare a composite nanofluid.
[0024] Furthermore, the mass ratio of the carbon nitride nanofluid to the molybdenum disulfide nanofluid is 1:1.
[0025] Beneficial effects of the present invention:
[0026] The present invention provides an environmentally friendly high-temperature resistant coated sand and a preparation process thereof. By adjusting the composition and process, the prepared ammonia-free coated sand not only conforms to the environmental protection concept, but also has good high-temperature resistance, high strength, high tensile strength and high stability.
[0027] The existing process adopts a non-phenolic resin system to prepare coated sand, and generally prepares phosphate inorganic coated sand by cold method and hot method, which reduces the gas emission of the coated sand, but the production process is more complicated, and there are disadvantages such as the core shooting and molding process are not easy to control; in the present invention, o-cresol epoxy resin is used instead of thermoplastic phenolic resin as a binder, and the resin is cured and formed by the ring-opening reaction of the epoxy group. The reaction process does not release small molecular harmful gases such as ammonia, which meets environmental protection requirements; and an acid curing agent containing active hydrogen is used instead of hexamethylenetetramine, and other additives are added to prepare environmentally friendly coated sand.
[0028] Ureapropyltriethoxysilane is used as a silane coupling agent. Its molecules contain amino and imino structures, which can form hydrogen bonds with the oxygen in the o-cresol epoxy resin molecules, enhance the interaction force, and better combine with the resin, thereby improving the thermal strength of the coated sand.
[0029] The composite fiber nanocrystal aerogel is introduced into the o-cresol epoxy resin to improve the high temperature resistance of the coated sand, and the introduction of the composite fiber nanocrystal aerogel can also be used as a binder for the original sand to improve the thermal strength of the coated sand; the composite fiber nanocrystal aerogel of the invention is a spherical material with a core-shell structure prepared by assembling the ionic crosslinking of divalent copper ions and carboxyl groups and the coordination bonding of divalent copper ions and trimesic acid organic ligands, the inner core is a three-dimensional network structure formed by fiber nanocrystals and carboxymethyl chitosan, which effectively improves the tensile strength and toughness of the coated sand; the outer shell structure is a dense MOF-199, which greatly improves the bonding degree between the composite fiber nanocrystal aerogel and the o-cresol epoxy resin and the original sand, thereby effectively improving the homogeneity of the coated sand.
[0030] In the present invention, ionic liquid is used as a dispersant to perform non-covalent modification on carbon nitride and molybdenum disulfide so as to effectively disperse them; both graphite-like carbon nitride and molybdenum disulfide have high thermal conductivity and low shear lubricity, but are typical easy-to-cluster particles and are not easy to disperse in water or many other organic solvents, so their practical applications are subject to many restrictions.
[0031] Using 3-(benzothiazole-2-mercapto)propane sulfonic acid as anion and tetrabutylphosphonium bromide as a cation, a heterocyclic sulfonate ionic liquid was prepared, which has the characteristics of non-volatility, high decomposition temperature, working temperature above 200°C, and has certain friction reduction and anti-wear functions. As a graphite-like phase carbon nitride and molybdenum disulfide are cross-linked and adsorbed with each other by heterocyclic sulfonate ionic liquid, the graphite-like phase carbon nitride and molybdenum disulfide can generate a stacked adsorption cluster with "bearing-like" structural characteristics at the friction interface, so that the two particles work synergistically to enhance the friction reduction and anti-wear performance and heat transfer performance.
[0032] Moreover, the mercapto group of the ionic liquid in the composite nanofluid produces a click reaction with the double bonds in the vinyl silicone oil, thereby increasing the binding force between the vinyl silicone oil and the coated sand, and synergistically increasing the moisture resistance of the coated sand. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, back, etc., the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0035] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0036] Example 1
[0037] A preparation process of environmentally friendly high temperature resistant coated sand, comprising the following steps:
[0038] The raw sand is dried, ureapropyl triethoxysilane is added and mixed, the temperature is raised to 140°C and transferred to a sand mixer, o-cresol epoxy resin and composite fiber nanocrystalline aerogel are added to mix the sand; the temperature is lowered to 125°C, composite nanofluid and curing accelerator are added and mixed, the temperature is lowered to 80°C, curing agent is added, sand is removed, crushed, sieved, vinyl silicone oil is added and mixed evenly, and an environmentally friendly and high temperature resistant coated sand is obtained;
[0039] The raw material composition of the environmentally friendly high temperature resistant coated sand is as follows: 70 parts of raw sand, 0.5 parts of ureapropyl triethoxysilane, 15 parts of o-cresol epoxy resin, 1 part of composite fiber nanocrystalline aerogel, 6 parts of composite nanofluid, 0.4 parts of curing accelerator, 5 parts of curing agent, and 0.5 parts of vinyl silicone oil; the curing accelerator is 2-ethyl-4-methylimidazole; the mass ratio of the curing accelerator to the curing agent is 8%;
[0040] The curing agent is obtained by mixing boric acid, citric acid and silicic acid in a mass ratio of 1:1:1;
[0041] The preparation of the composite fiber nanocrystalline aerogel comprises the following steps: 31.2 mg of carboxymethyl chitosan, 0.057 mmol, and 4 mL of a 2.6 mg / mL carboxylated fiber nanocrystalline suspension (w:w, 1:2) are mixed and stirred for 20 min, and then added to 100 mL of an aqueous solution of 20 mg / mL copper acetate monohydrate, and allowed to stand, separated, and washed to obtain copper-based hydrogel balls; 1 g of copper-based hydrogel balls, 30 mg of trimesic acid, 10 mL of deionized water, and 10 mL of ethanol are mixed, the pH value of the solution is adjusted to 3.1, and stirred for 1 h. After replacing the solvent with tert-butyl alcohol, the solution is freeze-dried to obtain a composite fiber nanocrystalline aerogel;
[0042] The preparation of the composite nanofluid includes the following steps:
[0043] 1) 50 mmol of tetrabutylphosphonium bromide, 100 mmol of sodium 3-(benzothiazole-2-mercapto)propane sulfonate and 100 mL of methanol were mixed, stirred at 55° C. for 46 h, filtered, 100 mL of acetonitrile was added, filtered, 100 mL of dichloromethane was added, washed with deionized water, and dried to obtain an ionic liquid;
[0044] 2) 2.8 mg of ionic liquid and 1.2 mg of carbon nitride were mixed and ground for 5-10 min, 100 mL of deionized water was added and the mixture was further ground for 5 min, and ultrasonically stirred for 20 min to obtain carbon nitride nanofluid;
[0045] 3) 2.8 mg of ionic liquid and 1.2 mg of molybdenum disulfide were mixed and ground for 5 min, 0.1 mg of gum arabic and 100 mL of deionized water were added and ground for 5 min, and ultrasonically stirred for 20 min to obtain a molybdenum disulfide nanofluid;
[0046] 4) The carbon nitride nanofluid and the molybdenum disulfide nanofluid were mixed and ultrasonically stirred for 20 minutes to prepare a composite nanofluid.
[0047] Example 2
[0048] A preparation process of environmentally friendly high temperature resistant coated sand, comprising the following steps:
[0049] The raw sand is dried, ureapropyl triethoxysilane is added and mixed, the temperature is raised to 145°C and transferred to a sand mixer, o-cresol epoxy resin and composite fiber nanocrystalline aerogel are added to mix the sand; the temperature is lowered to 128°C, composite nanofluid and curing accelerator are added and mixed, the temperature is lowered to 90°C, curing agent is added, sand is removed, crushed, sieved, vinyl silicone oil is added and mixed evenly, and an environmentally friendly high temperature resistant coated sand is obtained;
[0050] The raw material composition of the environmentally friendly high temperature resistant coated sand is as follows: 80 parts of raw sand, 0.8 parts of ureapropyl triethoxysilane, 20 parts of o-cresol epoxy resin, 2 parts of composite fiber nanocrystalline aerogel, 10 parts of composite nanofluid, 0.63 parts of curing accelerator, 7 parts of curing agent, and 0.8 parts of vinyl silicone oil; the curing accelerator is 2-ethyl-4-methylimidazole; the mass ratio of the curing accelerator to the curing agent is 9%;
[0051] The curing agent is obtained by mixing boric acid, citric acid and silicic acid in a mass ratio of 1:1:1;
[0052] The preparation of the composite fiber nanocrystalline aerogel comprises the following steps: 31.2 mg of carboxymethyl chitosan, 0.057 mmol, and 4 mL of a 2.6 mg / mL carboxylated fiber nanocrystalline suspension (w:w, 1:2) are mixed and stirred for 25 min, and then added to 100 mL of an aqueous solution of 20 mg / mL copper acetate monohydrate, and allowed to stand, separated, and washed to obtain copper-based hydrogel balls; 1 g of copper-based hydrogel balls, 30 mg of trimesic acid, 10 mL of deionized water, and 10 mL of ethanol are mixed, the pH value of the solution is adjusted to 3.1, and stirred for 1.5 h. After replacing the solvent with tert-butyl alcohol, the solution is freeze-dried to obtain a composite fiber nanocrystalline aerogel;
[0053] The preparation of the composite nanofluid includes the following steps:
[0054] 1) 50 mmol of tetrabutylphosphonium bromide, 100 mmol of sodium 3-(benzothiazole-2-mercapto)propane sulfonate and 100 mL of methanol were mixed, stirred at 58° C. for 45 h, filtered, 100 mL of acetonitrile was added, filtered, 100 mL of dichloromethane was added, washed with deionized water, and dried to obtain an ionic liquid;
[0055] 2) 2.8 mg of ionic liquid and 1.2 mg of carbon nitride were mixed and ground for 5-10 min, 100 mL of deionized water was added and the mixture was further ground for 5 min, and ultrasonically stirred for 25 min to obtain carbon nitride nanofluid;
[0056] 3) 2.8 mg of ionic liquid and 1.2 mg of molybdenum disulfide were mixed and ground for 8 min, 0.1 mg of gum arabic and 100 mL of deionized water were added and ground for 5 min, and ultrasonically stirred for 25 min to obtain a molybdenum disulfide nanofluid;
[0057] 4) The carbon nitride nanofluid and the molybdenum disulfide nanofluid were mixed and ultrasonically stirred for 25 minutes to prepare a composite nanofluid.
[0058] Example 3
[0059] A preparation process of environmentally friendly high temperature resistant coated sand, comprising the following steps:
[0060] The raw sand is dried, ureapropyl triethoxysilane is added and mixed, the temperature is raised to 150°C and transferred to a sand mixer, o-cresol epoxy resin and composite fiber nanocrystalline aerogel are added and mixed; the temperature is lowered to 130°C and composite nanofluid and curing accelerator are added and mixed, the temperature is lowered to 95°C and curing agent is added, the sand is removed, crushed, sieved, vinyl silicone oil is added and mixed evenly, and an environmentally friendly and high temperature resistant coated sand is obtained;
[0061] The raw material composition of the environmentally friendly high temperature resistant coated sand is as follows: 85 parts of raw sand, 1 part of ureapropyl triethoxysilane, 25 parts of o-cresol epoxy resin, 3 parts of composite fiber nanocrystalline aerogel, 12 parts of composite nanofluid, 1 part of curing accelerator, 10 parts of curing agent, and 1 part of vinyl silicone oil; the curing accelerator is 2-ethyl-4-methylimidazole; the mass ratio of the curing accelerator to the curing agent is 10%;
[0062] The curing agent is obtained by mixing boric acid, citric acid and silicic acid in a mass ratio of 1:1:1;
[0063] The preparation of the composite fiber nanocrystalline aerogel comprises the following steps: 31.2 mg of carboxymethyl chitosan, 0.057 mmol, and 4 mL of a 2.6 mg / mL carboxylated fiber nanocrystalline suspension (w:w, 1:2) are mixed and stirred for 30 min, and then added to 100 mL of an aqueous solution of 20 mg / mL copper acetate monohydrate, and allowed to stand, separated, and washed to obtain copper-based hydrogel balls; 1 g of copper-based hydrogel balls, 30 mg of trimesic acid, 10 mL of deionized water, and 10 mL of ethanol are mixed, the pH value of the solution is adjusted to 3.1, and stirred for 2 h. After replacing the solvent with tert-butyl alcohol, the solution is freeze-dried to obtain a composite fiber nanocrystalline aerogel;
[0064] The preparation of the composite nanofluid includes the following steps:
[0065] 1) Mix 50 mmol of tetrabutylphosphonium bromide, 100 mmol of sodium 3-(benzothiazole-2-mercapto)propane sulfonate and 100 mL of methanol, stir at 60° C. for 44 h, filter, add 100 mL of acetonitrile, filter, add 100 mL of dichloromethane, wash with deionized water, and dry to obtain an ionic liquid;
[0066] 2) 2.8 mg of ionic liquid and 1.2 mg of carbon nitride were mixed and ground for 10 min, 100 mL of deionized water was added and the mixture was further ground for 5 min, and ultrasonically stirred for 30 min to obtain carbon nitride nanofluid;
[0067] 3) 2.8 mg of ionic liquid and 1.2 mg of molybdenum disulfide were mixed and ground for 10 min, 0.1 mg of gum arabic and 100 mL of deionized water were added and ground for 5 min, and ultrasonically stirred for 30 min to obtain a molybdenum disulfide nanofluid;
[0068] 4) The carbon nitride nanofluid and the molybdenum disulfide nanofluid were mixed and ultrasonically stirred for 30 minutes to prepare a composite nanofluid.
[0069] Comparative Example 1
[0070] Example 3 was used as a control group, in which the composite fiber nanocrystal aerogel was replaced with carboxylated fiber nanocrystals, and the other processes were normal.
[0071] Comparative Example 2
[0072] Example 3 was used as a control group, in which no ionic liquid was prepared and other processes were normal.
[0073] Comparative Example 3
[0074] Example 3 was used as a control group, in which the composite nanofluid was replaced by carbon nitride, and the other processes were normal.
[0075] Comparative Example 4
[0076] Example 3 was used as a control group, in which the composite nanofluid was replaced by molybdenum disulfide, and the other processes were normal.
[0077] Comparative Example 5
[0078] Example 3 was used as a control group, in which no vinyl silicone oil was added and other processes were normal.
[0079] Comparative Example 6
[0080] Example 3 was used as a control group, in which ureapropyltriethoxysilane was replaced with trimethylsilane, and other processes were normal.
[0081] The sources of raw materials used in the above examples and comparative examples are:
[0082] Raw sand (50 mesh Dalin sand): Guangxi Lanke Resource Recycling Co., Ltd.; Ureapropyl triethoxysilane 23779-32-0: Hubei Jusheng Technology Co., Ltd.; o-cresol epoxy resin EOCN6850: Hunan Jiashengde Material Technology Co., Ltd.; Vinyl silicone oil V909624, 2-ethyl-4-methylimidazole E808801, boric acid B802844, citric acid C805019, silicic acid S902507, carboxymethyl chitosan C914893, trimesic acid T819407, tetrabutyl phosphonium bromide T819229, Sodium 3-(benzothiazole-2-mercapto)propane sulfonate S818451: Shanghai MacLean Biochemical Technology Co., Ltd.; carboxylated fiber nanocrystals, molybdenum disulfide 1317-33-5: Shanghai Koraman Reagent Co., Ltd.; copper acetate monohydrate 6046-93-1, carbon nitride AF744: Shanghai Xianding Biotechnology Co., Ltd.; ethanol, tert-butanol, methanol, acetonitrile, analytical grade: Sinopharm Reagent; dichloromethane D65100: Sigma-Aldrich (Shanghai) Trading Co., Ltd.; gum arabic S11034: Shanghai Yuanye Biotechnology Co., Ltd.
[0083] Performance test: refer to JB / T8583-2008 "Coated Sand for Casting" to test the hot tensile and bending strength as well as the tensile and bending strength at room temperature; cut into a size of 22.36mm×11.18mm×70mm, use SWY hydraulic strength test machine for testing, heat the sample mold and the upper and lower heating plates to 232℃, pour the coated sand from the sand hopper into the mold, and place the scraper plate perpendicular to the mold to scrape off the excess sand and press it on the heating plate for 2 minutes;
[0084] After taking it out, put it into the sample machine immediately and load it until it breaks. The test is completed within 10 seconds, which is the hot bending strength. Its bending strength is 16 times the tensile scale value in the pressure gauge; it is naturally cooled to 25℃ and measured within 1 hour as the room temperature bending strength. The test results refer to GB / T2684, and its bending strength is 16 times the tensile scale value in the pressure gauge; (The test bending strength is the smooth surface of the sample on the supporting edge); the specific results are shown in Table 1;
[0085]
[0086]
[0087] Table 1
[0088] The present invention provides an environmentally friendly high-temperature resistant coated sand and a preparation process thereof. By adjusting the composition and process, the prepared ammonia-free coated sand not only conforms to the environmental protection concept, but also has good high-temperature resistance, high strength, high tensile strength and high stability.
[0089] By comparing Example 3 with Comparative Example 1, it can be seen that the high temperature resistance of the coated sand is improved by introducing the composite fiber nanocrystalline aerogel into the o-cresol epoxy resin, and the introduction of the composite fiber nanocrystalline aerogel can also be used as a binder for the original sand to improve the thermal strength of the coated sand; the composite fiber nanocrystalline aerogel of the present invention is a spherical material with a core-shell structure prepared by assembling the ionic crosslinking of divalent copper ions and carboxyl groups and the coordination bonding of divalent copper ions and trimesic acid organic ligands, and the inner core is a three-dimensional network structure formed by fiber nanocrystals and carboxymethyl chitosan, which effectively improves the tensile strength and toughness of the coated sand; the outer shell structure is a dense MOF-199, which greatly improves the bonding degree between the composite fiber nanocrystalline aerogel and the o-cresol epoxy resin and the original sand, thereby effectively improving the homogeneity of the coated sand.
[0090] By comparing Example 3 with Comparative Example 2, it can be seen that a heterocyclic sulfonate ionic liquid is prepared using 3-(benzothiazole-2-mercapto)propane sulfonic acid as an anion and tetrabutyl phosphonium bromide as a cation. The heterocyclic sulfonate ionic liquid has the characteristics of being non-volatile, having a high decomposition temperature, and having an operating temperature above 200°C. It also has certain friction reduction and anti-wear functions, thereby improving the thermal stability of the coated sand.
[0091] By comparing Example 3 with Comparative Example 3 and Comparative Example 4, it can be seen that as graphite-like carbon nitride and molybdenum disulfide, they are cross-linked and adsorbed with each other by using heterocyclic sulfonate ionic liquid, so graphite-like carbon nitride and molybdenum disulfide can produce a stacked adsorption cluster with "bearing-like" structural characteristics at the friction interface, so that the two kinds of particles act synergistically to enhance the friction reduction and anti-wear properties and heat transfer properties, thereby improving the thermal stability of the coated sand.
[0092] By comparing Example 3 with Comparative Example 5, it can be seen that the mercapto group of the ionic liquid in the composite nanofluid produces a click reaction with the double bonds in the vinyl silicone oil, thereby improving the binding force between the vinyl silicone oil and the coated sand, and synergistically improving the moisture resistance of the coated sand.
[0093] By comparing Example 3 with Comparative Example 6, it can be seen that ureapropyl triethoxysilane is used as a silane coupling agent, and its molecule contains amino and imino structures, which can form hydrogen bonds with oxygen in the o-cresol epoxy resin molecule, enhance the interaction force, and better combine with the resin, thereby improving the thermal strength of the coated sand.
[0094] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A process for preparing environmentally friendly high temperature resistant coated sand, characterized in that: The following steps are involved: The raw sand is dried, ureapropyl triethoxysilane is added and mixed, the temperature is raised to 140-150°C and transferred to a sand mixer, o-cresol epoxy resin and composite fiber nanocrystalline aerogel are added and mixed; the temperature is lowered to 125-130°C, composite nanofluid and curing accelerator are added and mixed, the temperature is lowered to 80-95°C, curing agent is added, sand is removed, crushed, sieved, vinyl silicone oil is added and mixed evenly, and an environmentally friendly high temperature resistant coated sand is obtained; The preparation of composite nanofluids includes the following steps: 1) Tetrabutylphosphonium bromide, sodium 3-(benzothiazole-2-mercapto)propane sulfonate and methanol are mixed, stirred at 55-60° C. for 44-46 hours, filtered, acetonitrile is added, filtered, dichloromethane is added, washed with deionized water, and dried to obtain an ionic liquid; 2) Grinding the ionic liquid and carbon nitride for 5-10 minutes, adding deionized water and continuing grinding for 5 minutes, and ultrasonically stirring for 20-30 minutes to obtain carbon nitride nanofluid; 3) the ionic liquid and molybdenum disulfide were mixed and ground for 5-10 minutes, gum arabic and deionized water were added and ground for 5 minutes, and ultrasonically stirred for 20-30 minutes to obtain a molybdenum disulfide nanofluid; 4) mixing the carbon nitride nanofluid and the molybdenum disulfide nanofluid, and stirring them ultrasonically for 20-30 minutes to prepare a composite nanofluid; The preparation of composite fiber nanocrystalline aerogel includes the following steps: mixing carboxymethyl chitosan and carboxylated fiber nanocrystalline suspension for 20-30 minutes, adding to copper acetate monohydrate aqueous solution, standing, separating, washing, and obtaining copper-based hydrogel balls; mixing copper-based hydrogel balls, trimesic acid, deionized water, and ethanol, adjusting the pH value of the solution to 3.1, stirring for 1-2 hours, replacing the solvent with tert-butyl alcohol, and freeze-drying to obtain composite fiber nanocrystalline aerogel.
2. The process for preparing the environmentally friendly and high temperature resistant coated sand according to claim 1, characterized in that: Calculated by mass, the raw material composition of the environmentally friendly and high temperature resistant coated sand is: 70-85 parts of raw sand, 0.5-1 parts of ureapropyl triethoxysilane, 15-25 parts of o-cresol epoxy resin, 1-3 parts of composite fiber nanocrystalline aerogel, 6-12 parts of composite nanofluid, 0.4-1 parts of curing accelerator, 5-10 parts of curing agent, and 0.5-1 parts of vinyl silicone oil.
3. The process for preparing the environmentally friendly and high temperature resistant coated sand according to claim 1, characterized in that: The curing accelerator is 2-ethyl-4-methylimidazole.
4. The process for preparing the environmentally friendly and high temperature resistant coated sand according to claim 1, characterized in that: The mass ratio of the curing accelerator to the curing agent is 8-10%.
5. The process for preparing the environmentally friendly and high temperature resistant coated sand according to claim 1, characterized in that: The curing agent is obtained by mixing boric acid, citric acid and silicic acid in a mass ratio of 1:1:
1.
6. The process for preparing the environmentally friendly and high temperature resistant coated sand according to claim 1, characterized in that: In the preparation of the composite fiber nanocrystalline aerogel, the mass volume ratio of the copper-based hydrogel ball, trimesic acid, deionized water, and ethanol is 1 g:30 mg:10 mL:10 mL.
7. The process for preparing the environmentally friendly and high temperature resistant coated sand according to claim 1, characterized in that: In the preparation of the composite nanofluid, the mass ratio of carbon nitride nanofluid to molybdenum disulfide nanofluid is 1:
1.
8. An environmentally friendly and high temperature resistant coated sand, characterized in that: The method is prepared by the process described in any one of claims 1 to 7.